The time-frame of acute resistance exercise effects on football skill performance: The impact of exercise intensity - Draganidis, D.; Chatzinikolaou, A.; Jamurtas, A. Z.; Barbero, J. C.; Tsoukas, D.; Theodorou, A. S.; Margonis, K.; Michailidis, Y.; Avloniti, A.; Theodorou, A.; Kambas, A.; Fatouros, I. (Journal of Sports Sciences, 2013)
The purpose of this study was to determine the recovery rate of football skill performance following resistance exercise of moderate or high intensity. Ten elite football players participated in three different trials: control, low-intensity resistance exercise (4 sets, 8-10 repetitions/set, 65-70% 1 repetition maximum [1RM]) and high-intensity resistance exercise (4 sets, 4-6 repetitions/set, 85-90% 1RM) in a counterbalanced manner. In each experimental condition, participants were evaluated pre, post, and at 24, 48, 72 h post exercise time points. Football skill performance was assessed through the Loughborough Soccer Passing Test, long passing, dribbling, shooting and heading. Delayed onset muscle soreness, knee joint range of motion, and muscle strength (1RM) in squat were considered as muscle damage markers. Blood samples analysed for creatine kinase activity, C-reactive protein, and leukocyte count. Passing and shooting performance declined (P < 0.05) post-exercise following resistance exercise. Strength declined post-exercise following high-intensity resistance exercise. Both trials induced only a mild muscle damage and inflammatory response in an intensity-dependent manner. These results indicate that football skill performance is minimally affected by acute resistance exercise independent of intensity suggesting that elite players may be able to participate in a football practice or match after only 24 h following a strength training session.